Propuesta de una estrategia preventiva del cáncer cérvico uterino en la adolescencia mediante una revisión de la literatura científica - Chiluisa Proaño, Viviana Marisol (2025)
Cervical cancer (CC) is a significant cause of morbidity and mortality among women, being the second most common cancer. This cancer is preventable and curable, especially in developing countries, so reducing its incidence and mortality is crucial. Adolescence is a key stage to form preventive attitudes, and this research proposes a preventive strategy through a review of the scientific literature. Using a qualitative methodology of non-experimental and descriptive type, scientific articles, relevant studies published between 2017 and 2024 were reviewed. The results highlight the effectiveness of educational interventions to improve knowledge and preventive attitudes in adolescents, but also reveal barriers such as socioeconomic inequality, cultural barriers, and limited knowledge about HPV risk factors. It is proposed to create a blog specialized in CC that offers updated information on prevention, risk factors, methods of detection and treatment of CC, serving as an educational tool accessible to adolescents and women of all ages. This blog would include interactive sections, patient testimonials, and resources for health professionals, facilitating the dissemination of information in communities with limited access to health services. In conclusion, educational interventions are effective in increasing knowledge and positively changing attitudes towards the prevention of CC, but it is necessary to adapt and expand these strategies to overcome existing barriers and improve equity in access to health services, also addressing the emotional needs of patients.